The clinical use of bone graft substitutes in orthopedic surgery in Germany—A 10‐years survey from 2008 to 2018 of 1, 090, 167 surgical interventions. Issue 2 (22nd July 2021) - Rupp, Markus; Klute, Lisa; Baertl, Susanne; Walter, Nike; Mannala, Gopala‐Krishna; Frank, Leona; Pfeifer, Christian; Alt, Volker; Kerschbaum, Maximilian
Abstract: Aim of the study was to evaluate (1) the overall use of bone graft substitutes, autografts and allografts, (2) of different types of bone graft substitutes (calcium sulfate, calcium phosphate, calcium phosphate ceramics or polymethyl methacrylate) and of different bone grafts (cancellous vs. cortical), and (3) the use of antibiotic‐loading of bone graft substitutes in orthopedic surgery in Germany. Gross data were provided from the Federal Statistical Office of Germany and revealed an overall increase in bone defect reconstruction procedures using bone graft substitutes, autografts and allografts from 86, 294 in 2008 to 99, 863 cases in 2018 (+15.7%). The relative use of bone graft substitutes for these interventions strongly increased from 11.8% in 2008 (10, 163 cases) to 23.9% in 2018 (23, 838 cases) with an increase of +134.4%. Furthermore, antibiotic‐loaded bone graft substitutes were implanted more frequently with an overall increase of +194% (2008: n  = 2, 657; 2018: n  = 7, 811). The work shows an increasing use of bone graft substitutes and antibiotic‐loaded bone graft substitutes over the last 10 years in Germany.